Return to sport: First data from the Nationwide German Myocarditis Registry for athletes - Schellhorn, P. S.; Burgstahler, C.; Rokitzki, J.; Nieß, A. M. (Translational Sports Medicine, 2020)
here is currently no evidence how to treat athletes with suspected or proven myocarditis in the context of "return to sport" (RTS). Addressing this issue, a multi-centre, web-based online registry was initiated in 2011 to record athletes presenting with suspected or proven myocarditis. Our nationwide registry is the first successfully implemented database of competitive athletes with suspected or proven myocarditis. Besides baseline data, available clinical data and the physician`s recommendation in terms of sport participation were recorded. A telephone interview for clinical follow-up was performed one year (1FU) after the initial presentation. 98 athletes (77 males, mean age 30.9 years) were analysed. Data from 1FU were available for 74 athletes. At baseline, 72% of the athletes reported infection-associated symptoms prior to the first medical contact. A high percentage of athletes present abnormal clinical or technical cardiac findings. Abnormal rest-ECG was seen in 41/74 athletes, abnormal echo in 37/74, abnormal MRI in 32/74. During the period prior to 1FU, there were no incidences of sudden death or cardiac arrest. Most athletes return to sport within one year, however duration and intensity of training were still reduced in one third of the athletes. A total of 58/74 were fully reintegrated in sport, 10/74 partially, and 5/74 were not able to participate in sport. Greater age was delineated as the only significant predictor for incomplete reintegration after one year. Consequently, even if there is missing evidence regarding how to treat athletes with suspected myocarditis in context of RTS, the chosen approach in terms of diagnostic work-up and decision regarding RTS seems to be safe. In summary, treating athletes with suspected or proven myocarditis continues to be challenging but register data will help to get a more precise idea how to treat athletes with myocarditis.